Descriptive Analysis Sociodemography of Breastfeeding Mother in Suku Anak Dalam During Covid-19 Pandemic - vittria meilinda; Eka Rinalia (Science Midwifery, 2022)
Now moment now this the problem of Covid-19 in Indonesia already start sloping however no could denied that mother breastfeed must exists enhancement power stand body especially baby with breastfeeding , breastfeeding becomes very good protection for baby. Effect Breast milk protection is very strong in fighting disease infections through increased power hold on baby. The purpose of this study to determine the characteristics mother breast-feed in Suku Anak Dalam in on period pandemic . Quantitative research methods , design cross-sectional with a total sampling of 58 respondents mother breast-feed in Suku Anak dalam , data collection is done through observation and questionnaire . Results study obtained 98.3% of mothers no work , 58.6% mother no take formal education , 62.1% range age mother reproduction , 77.6% mother have child ≥ 3, 98.3% mother going through a normal childbirth process is not in service health , 94.8% Mother argue that breast milk can replaced with other foods as well as 98.3% mothers provide complementary foods aged <6 months. Concluded description from sociodemography on mother breastfeeding in the tribe child in must very noticed and need maximizing facility and service health especially continuity health on mother and child with maximizing program management lactation , as well with condition moment now this need exists cooperation cross- sector and cross program inside even distribution service excellent health.